Breeding experience and pair bond duration both increase reproductive success in an avian cooperative breeder - Guy Beauchamp; Tori D. Bakley; John W. Fitzpatrick; Sahas Barve (Animal Behaviour, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Food, weather, and population density, not number of helpers, drive overwinter survival in Florida Scrub-Jays - Guy Beauchamp; Tori D. Bakley; John W. Fitzpatrick; Sahas Barve (Oecologia, 2025)

Density dependence maintains long‐term stability despite increased isolation and inbreeding in the Florida Scrub‐Jay - Jeremy Summers; Elissa J. Cosgrove; Reed Bowman; John W. Fitzpatrick; Nancy Chen (Ecology Letters, 2024)
Isolation caused by anthropogenic habitat fragmentation can destabilize populations. Populations relying on the inflow of immigrants can face reduced fitness due to inbreeding depression as fewer new individuals arrive. Empirical studies of the demographic consequences of isolation are critical to understand how populations persist through changing conditions. We used a 34‐year demographic and environmental dataset from a population of cooperatively breeding Florida Scrub‐Jays ( Aphelocoma coerulescens ) to create mechanistic models linking environmental and demographic factors to population growth rates. We found that the population has not declined despite both declining immigration and increasing inbreeding, owing to a coinciding response in breeder survival. We find evidence of density‐dependent immigration, breeder survival and fecundity, indicating that interactions between vital rates and local density play a role in buffering the population against change. Our study elucidates the impacts of isolation on demography and how long‐term stability is maintained via demographic responses.

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Short-tailed shearwater (Ardenna tenuirostris) plastic loads and particle dimensions exhibit spatiotemporal similarity in the Pacific Ocean - Gary W. Shugart; Cheyenne L. Waters; John D. FitzPatrick; Robert S.A. Kaler; Lucy S. Vlietstra (Marine Pollution Bulletin, 2023)

Simulating flood events at the Twin Ports of Duluth-Superior using a linked hydrologic-hydrodynamic framework - Lindsay Fitzpatrick; Daniel Titze; Eric J. Anderson; Dmitry Beletsky; John G. W. Kelley (Ocean Dynamics, 2023)
Generally, ports in the North American Great Lakes are not supported with navigational guidance (water level, water temperature, currents, ice) by NOAA’s Great Lakes Operational Forecast System (GLOFS). To examine the benefit of extending model coverage to this critical infrastructure, a linked hydrologic-hydrodynamic framework was developed for the Twin Ports of Duluth-Superior in western Lake Superior, and tested over three case studies of flooding due to storm surge and/or river flooding. Streamflow from 22 National Water Model (NWM) simulated and 3 gauged inflows within the domain was injected into a hydrodynamic model built on the Finite Volume Community Ocean Model (FVCOM), with a wet-dry grid that covered the harbor and surrounding floodplain. Model results from flood simulations compared well against time-series of water level and streamflow at gauges within the harbor, with root mean square error (RMSE) and bias values small relative to the typical fluctuations. Inclusion of NWM-simulated tributaries improved the accuracy of modeled water levels in the harbor, and increased simulated current speeds in navigational channels by up to 0.5 ms −1 . Modeled inundation extent in the floodplain closely matched flood extent surveys conducted in response to a record flood event in 2012, demonstrating the capability of the modeling framework to provide flood guidance in the complex coastal setting.

The structure and organisation of an Amazonian bird community remains little changed after nearly four decades in Manu National Park - Ari E. Martínez; José M. Ponciano; Juan P. Gomez; Thomas Valqui; Jorge Novoa; Mariamercedes Antezana; Gabriela Biscarra; Ettore Camerlenghi; Blaine H. Carnes; Renato Huayanca Munarriz; Eliseo Parra; Isabella M. Plummer; et al. (Ecology Letters, 2023)
Documenting patterns of spatiotemporal change in hyper‐diverse communities remains a challenge for tropical ecology yet is increasingly urgent as some long‐term studies have shown major declines in bird communities in undisturbed sites. In 1982, Terborgh et al. quantified the structure and organisation of the bird community in a 97‐ha. plot in southeastern Peru. We revisited the same plot in 2018 using the same methodologies as the original study to evaluate community‐wide changes. Contrary to longitudinal studies of other neotropical bird communities (Tiputini, Manaus, and Panama), we found little change in community structure and organisation, with increases in 5, decreases in 2 and no change in 7 foraging guilds. This apparent stability suggests that large forest reserves such as the Manu National Park, possibly due to regional topographical influences on precipitation, still provide the conditions for establishing refugia from at least some of the effects of global change on bird communities.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

How will climate novelty influence ecological forecasts? Using the Quaternary to assess future reliability - Matthew C. Fitzpatrick; Jessica L. Blois; John W. Williams; Diego Nieto‐Lugilde; Kaitlin C. Maguire; David J. Lorenz (Global Change Biology, 2018)
Future climates are projected to be highly novel relative to recent climates. Climate novelty challenges models that correlate ecological patterns to climate variables and then use these relationships to forecast ecological responses to future climate change. Here, we quantify the magnitude and ecological significance of future climate novelty by comparing it to novel climates over the past 21,000 years in North America. We then use relationships between model performance and climate novelty derived from the fossil pollen record from eastern North America to estimate the expected decrease in predictive skill of ecological forecasting models as future climate novelty increases. We show that, in the high emissions scenario (RCP 8.5) and by late 21st century, future climate novelty is similar to or higher than peak levels of climate novelty over the last 21,000 years. The accuracy of ecological forecasting models is projected to decline steadily over the coming decades in response to increasing climate novelty, although models that incorporate co‐occurrences among species may retain somewhat higher predictive skill. In addition to quantifying future climate novelty in the context of late Quaternary climate change, this work underscores the challenges of making reliable forecasts to an increasingly novel future, while highlighting the need to assess potential avenues for improvement, such as increased reliance on geological analogs for future novel climates and improving existing models by pooling data through time and incorporating assemblage‐level information.

An experimental test of alternative population augmentation scenarios - John A. Kronenberger; Jill C. Gerberich; Sarah W. Fitzpatrick; E. Dale Broder; Lisa M. Angeloni; W. Chris Funk (Conservation Biology, 2018)
Human land use is fragmenting habitats worldwide and inhibiting dispersal among previously connected populations of organisms, often leading to inbreeding depression and reduced evolutionary potential in the face of rapid environmental change. To combat this augmentation of isolated populations with immigrants is sometimes used to facilitate demographic and genetic rescue. Augmentation with immigrants that are genetically and adaptively similar to the target population effectively increases population fitness, but if immigrants are very genetically or adaptively divergent, augmentation can lead to outbreeding depression. Despite well‐cited guidelines for the best practice selection of immigrant sources, often only highly divergent populations remain, and experimental tests of these riskier augmentation scenarios are essentially nonexistent. We conducted a mesocosm experiment with Trinidadian guppies (Poecilia reticulata) to test the multigenerational demographic and genetic effects of augmenting 2 target populations with 3 types of divergent immigrants. We found no evidence of demographic rescue, but we did observe genetic rescue in one population. Divergent immigrant treatments tended to maintain greater genetic diversity, abundance, and hybrid fitness than controls that received immigrants from the source used to seed the mesocosms. In the second population, divergent immigrants had a slightly negative effect in one treatment, and the benefits of augmentation were less apparent overall, likely because this population started with higher genetic diversity and a lower reproductive rate that limited genetic admixture. Our results add to a growing consensus that gene flow can increase population fitness even when immigrants are more highly divergent and may help reduce uncertainty about the use of augmentation in conservation.

Population demography and heterozygosity–fitness correlations in natural guppy populations: An examination using sexually selected fitness traits - Catherine E. Grueber; John L. Fitzpatrick; Alessandro Devigili; Clelia Gasparini; Indar W. Ramnarine; Jonathan P. Evans (Molecular Ecology, 2017)
Heterozygosity–fitness correlations ( HFC s) have been examined in a wide diversity of contexts, and the results are often used to infer the role of inbreeding in natural populations. Although population demography, reflected in population‐level genetic parameters such as allelic diversity or identity disequilibrium, is expected to play a role in the emergence and detectability of HFC s, direct comparisons of variation in HFC s across many populations of the same species, with different genetic histories, are rare. Here, we examined the relationship between individual microsatellite heterozygosity and a range of sexually selected traits in 660 male guppies from 22 natural populations in Trinidad. Similar to previous studies, observed HFC s were weak overall. However, variation in HFC s among populations was high for some traits (although these variances were not statistically different from zero). Population‐level genetic parameters, specifically genetic diversity levels (number of alleles, observed/expected heterozygosity) and measures of identity disequilibrium (g2 and heterozygosity–heterozygosity correlations), were not associated with variation in population‐level HFC s. This latter result indicates that these metrics do not necessarily provide a reliable predictor of HFC effect sizes across populations. Importantly, diversity and identity disequilibrium statistics were not correlated, providing empirical evidence that these metrics capture different essential characteristics of populations. A complex genetic architecture likely underpins multiple fitness traits, including those associated with male fitness, which may have reduced our ability to detect HFC s in guppy populations. Further advances in this field would benefit from additional research to determine the demographic contexts in which HFC s are most likely to occur.

Close agreement between pollen‐based and forest inventory‐based models of vegetation turnover - Diego Nieto‐Lugilde; Kaitlin C. Maguire; Jessica L. Blois; John W. Williams; Matthew C. Fitzpatrick (Global Ecology and Biogeography, 2015)
Aim Fossil records are being increasingly used to help understand the consequences of climate change for biodiversity. Pollen records from the late Q uaternary are among the most commonly used fossil data, but pollen‐based inferences of biodiversity can potentially be confounded by spatial and taxonomic uncertainties and the influence of non‐climatic abiotic factors such as soils on vegetation–climate relationships. Using paired pollen and vegetation inventories, we assess the fidelity of pollen‐based estimates of compositional turnover of vegetation along environmental gradients given various sources of uncertainty. Location E astern U nited S tates. Methods We used modern pollen records and forest composition data from F orest I nventory and A nalysis ( FIA ) plots to fit generalized dissimilarity models. To address how uncertainties in pollen records affect estimates of turnover, we coarsened the vegetation data spatially from individual plots to 10‐ and 30‐arcmin resolution and taxonomically from species to genus. To determine whether soil properties influenced turnover, we used deviance partitioning between models including climate or soil variables versus models with a combination of both. Results Pollen‐based estimates of turnover were highly correlated with those based on FIA data, but tended to be lower, mainly due to differences in taxonomic resolution and secondarily to differences in spatial resolution. Neither spatial nor taxonomic uncertainty substantially reduced the correlation between pollen‐ and FIA ‐based estimates of turnover. FIA data best matched pollen records when they were aggregated to genus and 30‐arcmin resolution. Vegetation–climate relationships were similar across datasets, although models sometimes differed. The influence of soil variables was negligible compared with climate variables and did not improve model fit. Pollen thresholds did not greatly affect the form and strength of pollen–vegetation relationships. Main conclusions Pollen can act as a robust proxy for vegetation turnover, thereby supporting the use of pollen‐based estimates of turnover to predict temporal changes in vegetation.

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

Hybridization between two gartersnake species (Thamnophis) of conservation concern: a threat or an important natural interaction? - John S. Placyk; Benjamin M. Fitzpatrick; Gary S. Casper; Randall L. Small; R. Graham Reynolds; Daniel W. A. Noble; Ronald J. Brooks; Gordon M. Burghardt (Conservation Genetics, 2012)

Attenuation of arthritis in rodents by a novel orally-available inhibitor of sphingosine kinase - Leo R. Fitzpatrick; Cecelia Green; Elizabeth E. Frauenhoffer; Kevin J. French; Yan Zhuang; Lynn W. Maines; John J. Upson; Emmanuel Paul; Henry Donahue; Timothy J. Mosher; Charles D. Smith (Inflammopharmacology, 2011)

Effects of Habitat Fragmentation on Effective Dispersal of Florida Scrub‐Jays - AURÉLIE COULON; JOHN W. FITZPATRICK; REED BOWMAN; IRBY J. LOVETTE (Conservation Biology, 2010)
Studies comparing dispersal in fragmented versus unfragmented landscapes show that habitat fragmentation alters the dispersal behavior of many species. We used two complementary approaches to explore Florida Scrub‐Jay (Aphelocoma cœrulescens) dispersal in relation to landscape fragmentation. First, we compared dispersal distances of color‐marked individuals in intensively monitored continuous and fragmented landscapes. Second, we estimated effective dispersal relative to the degree of fragmentation (as inferred from two landscape indexes: proportion of study site covered with Florida Scrub‐Jay habitat and mean distance to nearest habitat patch within each study site) by comparing genetic isolation‐by‐distance regressions among 13 study sites having a range of landscape structures. Among color‐banded individuals, dispersal distances were greater in fragmented versus continuous landscapes, a result consistent with other studies. Nevertheless, genetic analyses revealed that effective dispersal decreases as the proportion of habitat in the landscape decreases. These results suggest that although individual Florida Scrub‐Jays may disperse farther as fragmentation increases, those that do so are less successful as breeders than those that disperse short distances. Our study highlights the importance of combining observational data with genetic inferences when evaluating the complex biological and life‐history implications of dispersal .

Life and Death in the Fast Lane: Demographic Consequences of Road Mortality in the Florida Scrub‐Jay - Ronald L. Mumme; Stephan J. Schoech; Glen E. Woolfenden; John W. Fitzpatrick (Conservation Biology, 2000)
We examined the demographic consequences of road mortality in the cooperatively breeding Florida Scrub‐Jay (Aphelocoma coerulescens ), a threatened species restricted to the oak scrub of peninsular Florida. Between May 1986 and July 1995 we monitored the survival and reproductive success of a color‐banded population of jays along a two‐lane highway at Archbold Biological Station. Annual mortality of breeding adults was 0.38 on road territories, significantly higher than the rate of 0.23 for breeders on nonroad territories. High mortality on road territories appeared to be a direct result of automobile traffic per se and not a consequence of road‐induced changes in habitat characteristics. Mortality was especially high for immigrants without previous experience living along the road: in their first two years as breeders on road territories, naive immigrants experienced annual mortality of 0.50 and 0.45. From year 3 onward, however, annual mortality dropped to 0.29, not significantly different from the rate for birds on nonroad territories. This experience‐dependent decline in road mortality could be caused either by surviving jays learning to avoid automobiles or by selective mortality operating through time (demographic heterogeneity). Proximity to the road had no effect on nesting success beyond its indirect effects on breeder experience and group size. Because the mortality of 30‐ to 90‐day‐old fledglings was significantly higher on road territories than on nonroad territories, however, breeder mortality greatly exceeded production of yearlings on road territories. Roadside territories therefore are sinks that can maintain populations of Florida Scrub‐Jays only via immigration. Because Florida Scrub‐Jays do not avoid roadside habitats and may even be attracted to them, road mortality presents a difficult challenge for the management and conservation of this threatened and declining species.

Multi-locus DNA fingerprinting supports genetic monogamy in Florida scrub-jays - James S. Quinn; Glen E. Woolfenden; John W. Fitzpatrick; Bradley N. White (Behavioral Ecology and Sociobiology, 1999)

Contrasting patterns of elevational zonation for birds and mammals in the Andes of southeastern Peru - Bruce D. Patterson; Douglas F. Stotz; Sergio Solari; John W. Fitzpatrick; Victor Pacheco (Journal of Biogeography, 1998)
To determine the generality of avian diversity patterns, we investigated patterns of elevational zonation shown by birds and mammals along the eastern slope of the Andes Mountains in southeastern Peru. The strong environmental gradient sampled, entirely within Peru's Manu National Park and Biosphere Reserve, supports highly diverse faunas. Elevational distributions of 901 bird species, 129 bat species, and twenty‐eight species of native mice exhibit contrasting patterns in species richness, species composition, and species turnover. Birds and bats showed smooth declines of species richness with elevation, whereas the richness of mouse assemblages was unrelated to elevation. For all three groups, the greatest differences were between lowland and highland faunas, although cutoff points for this contrast varied among groups (≈ 500 m for birds, 750 m for bats, and 1000 m for mice). Differences in composition also separated bird and bat faunas on either side of c. 1400 m (the boundary between montance forest and cloud forest); for mice, this faunal transition may take place nearer to 2000 m. Bird and bat faunas lacked the more discrete zonations suggested for mouse assemblages, as indicated by elevational range profiles and nested subset analyses. Distinct highland assemblages are apparent in two‐dimensional histograms of range limits of birds and mice, but not for bats. Highland bat species occupy broader elevational ranges than lowland bat species, but for both birds and mice, species at intermediate elevations had the broadest amplitudes. Finally, clumping of range maxima and minima along the gradient identified zones of pronounced species turnover in each group, but these were generally not strongly associated with the locations of ecotones. Differences in zonation of these groups appear to reflect their different biological attributes and phylogenetic histories. Such differences obviously complicate discussions of ‘general’ diversity patterns, and limit the usefulness of birds to forecast or predict diversity patterns in other more poorly known groups—other groups may show elevated diversity and endemism in areas where avian diversity patterns appear unremarkable. The pronounced contrasts between bats and mice, and the generally intermediate character of avian patterns, suggest that future analyses might profitably partition birds into finer, more homogeneous groups of historically and/or ecologically similar species. Group differences in zonation may ultimately prove explicable with information on both species‐abundance patterns and resource distributions.